A Clinico-Hematological Profile of Dengue Outbreak Among Healthcare Professionals in A Tertiary Care Hospital of Ahmedabad with Analysis on Economic Impact - Jain, Abhinav; Shah, Asha N; Patel, Pinakin; Desai, Mitali; Somani, Shrikant; Parikh, Pallav; Singhal, Roopesh; Joshi, Dinesh (National Journal of Community Medicine, 2013)
Introduction: There has been a recent surge of Dengue infections in India, with many outbreaks in urban areas. This study is the biggest documented in-hospital dengue fever outbreak among health care personnel in India. Aims & objectives: To study the clinical and hematological profile of Dengue outbreak and its cost impact. Materials & methods: 56 patients from medical, dental and nursing fraternity with Dengue were studied. The cost of indoor treatment, investigations and loss of work were calculated. The cases were classified using the newer WHO Dengue classification (2009). Results & discussion: The commonest symptom was fever followed by myalgia. The commonest sign was delayed capillary filling. The most common abnormalities that predict severity were raised hematocrit of >40% and a low platelet count of <50,000/mm3. The outbreak produced a huge financial loss of Rs 19,48,800 with a loss of 6300 man-hours of doctors. The mortality rate was 1.7%, lower than average. Conclusion: Dengue has a huge economic impact and is largely preventable.